Unusual Effects of Penicillin G and Chloramphenicol on the Growth of Moraxella osloensis - DeLeys, Robert J. (1977)
Growth of exponential-phase liquid cultures of Moraxella osloensis was inhibited by 0.5 U of penicillin G per ml. For this organism, low concentrations of penicillin acted primarily in a bacteriostatic rather than in a bactericidal manner. At higher concentrations of penicillin some killing did take place, but the rate of killing was rather slow and appeared to be independent of penicillin concentration. Microscopic observation of cells from penicillin-treated cultures showed little or no cellular swelling or lysis. The total cell count did not decrease significantly during 6 h of incubation in 5,000 U of penicillin per ml. The rates of respiration, nucleic acid synthesis, and protein synthesis were not affected by the presence of penicillin. Attempts to counteract the bactericidal action of high concentrations of penicillin with growth inhibitory concentrations of chloramphenicol were unsuccessful, since chloramphenicol itself was more bactericidal than penicillin for M. osloensis.